Congenital Oral Squamous Cell Carcinoma in a Suckling Piglet. (14th October 2021) - Hattab, Jasmine; Trachtman, Abigail Rose; Tiscar, Pietro Giorgio; Di Domenico, Marco; Abbate, Jessica Maria; Ieni, Antonio; Marruchella, Giuseppe
Abstract : A 3-week-old suckling piglet spontaneously died after septicemic colibacillosis. At postmortem examination, bulging and ulcerated lesions were seen, affecting the oral mucosa on the inner surface of the lower lip. After histopathological investigation, the diagnosis of congenital oral squamous cell carcinoma was made. To the best of our knowledge, this is the first case of congenital oral squamous cell carcinoma ever described. A relationship has been shown or suggested between papillomavirus infection and oral squamous cell carcinoma in humans and animals. However, next-generation sequencing study did not demonstrate any papillomavirus sequences in the case reported herein.